The arbitral jurisdiction of the State Council - a comparative study - Hashim Sihoud, a teacher, Dr. Mitras (The college of law and political science journal, 2023)
For a long time, the efforts of public administration and law scholars havecombined in the search for the best legal and administrative ways to advance theprogress of administrative activity: legal frameworks were established to applymodern theories in management science. However, its activity still faces challengesand legal and realistic problems, and it is expected that they will remain as long as themanagement's activity is changing and renewed. That is why legal thought realizedthat solving these problems can only be achieved through quick solutions; Thisis because late solutions are no less dangerous than the problem remaining. Thatis why the advisory section of the State Council has been entrusted with the taskof settling disputes that arise between the administrative authorities, and thanksto this, two goals are achieved: speed and justice. The legal mechanisms used inexpressing legal opinion and advice are less complicated than the normal litigationprocedures, in addition to that. What the State Council has from the advantage ofbeing highly specialized: as the most knowledgeable, fastest responding and mostinsightful body in developing appropriate solutions to the requirements and needsof good governance. For this reason, legislators (in both Egypt and Iraq) chosethe State Council to take over this task through its advisory departments, with thedifference in some of the conditions necessary for its exercise.